Analisis Dampak Penyaluran Dana Zakat Produktif Terhadap UMKM Mustahik - Fathiya Rahma Ainun Izza; Arif Sapta Yuniarto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Empowering UMKM is one of the elements to improve the community's economy. The empowerment of UMKM can be done through productive zakat fund distribution activities by zakat management institutions. This research aims to analyze the impact of channeling productive zakat funds to UMKM Mustahik in LAZISMU DIY Region. This research uses quantitative research with a sampling technique with a purposive sampling technique. The analysis method used uses Simple Regression analysis with classical assumption testing. Based on the value of the coefficient of determination (R Square), namely R2 = 0.474 ×100% = 47.4%. This value shows that productive zakat funds affect mustahik MSMEs by 47.4%, while the remaining 52.6% is influenced by other factors. The results of this research show that productive zakat funds influence the development of UMKM mustahik.